PLA/Wollastonite composite filaments for 3D printing application: rheological properties and extrusion - Mohd Ikram Ramli,; Amaresh Malakar Choudhury,; Lem, Daniel Jie Choong; Teng, Jie Jun; Nishata Royan Rajendran Royan,; Meor Ahmad Faris Meor Tajudin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The 3D printing has fundamentally transformed the approach to object design and manufacturing, enabling the cost-effective production of intricate and customized components. This study aims to investigate the rheological and mechanical properties of Poly-lactic Acid (PLA)/Wollastonite (WA) composite filaments for 3D printing, particularly for bone implant applications. The powder composition used is 90 wt.% PLA and 10 wt.% WA. The blending process was conducted at a temperature of 190°C and a torque value of 30 rpm. Capillary rheometer testing was carried out at temperatures of 160 °C, 170 °C, and 180 °C on the feedstock. The rheological results of the feedstock show pseudoplastic flow behavior, where viscosity decreases with an increase in shear rate. The flow behavior indices obtained at all temperatures are 0.87, 0.79, and 0.49 respectively. At these temperatures, the flow behaviour index is below 1 (n<1), indicating pseudoplastic flow and compatible for the FDM process. The optimal filament extrusion parameters were determined to be 170°C, 190°C, 180°C, and 140°C for the four temperature zones, respectively, with a screw speed of 4.0 rpm and a spool speed of 40 mm/s. The Taguchi Method was employed to evaluate the filament’s quality and strength using three different printing settings. The density of the PLA-WA composite filament was 1.32 g/cm³. These results suggest that the PLA-WA composite has promising candidate use in 3D printing applications.